Eksplorasi Keterkaitan antara Pemahaman Membaca dan Penyelesaian Soal Cerita Matematika Pada Prestasi Belajar Siswa Kelas IV Sekolah Dasar - Fadhilah, Lutfiani Nur; Purnamasari, Veryliana; Sulianto, Joko (Innovative: Journal Of Social Science Research, 2025)
This study aims to explore the correlation between reading comprehension and the ability to solve mathematical word problems in relation to the academic achievement of fourth-grade elementary students. A descriptive qualitative method was used, employing Miles and Huberman’s data analysis model. Data were collected through interviews, observations, and written tests. The findings show that students with strong reading comprehension skills were able to solve word problems accurately, while those with low reading skills struggled. It can be concluded that reading comprehension is closely related to students’ performance in solving mathematical word problems.